ANALISIS WORK LIFE BALANCE TERHADAP PRESTASI MAHASISWA DAN MOTIVASI MAHASISWA SEBAGAI MODERASI PADA PRODI MANAJEMEN UBP KARAWANG - Suherman, Enjang; Suroso, Suroso (STMIK Pringsewu, 2024)
The current phenomenon is that quite a few students in private higher education act as workers which will have an impact on the balance of their personal and work lives. This work-life balance will certainly affect student achievement both in terms of time and role. However, student motivation can provide reinforcement for this balance in order to achieve academic achievement. This research aims to analyze the moderation of motivation on the influence of work life balance (WLB) on student achievement. The method used is a descriptive verification method with a purposive sampling technique, namely taking samples of students with worker status only. Meanwhile, the number of samples was 196 with the Lemeshow formula. The data collection used a questionnaire with a Likert scale. And data analysis uses SEM PLS analysis and descriptive statistics. The research results show that student WLB is balanced, student motivation is in the high category, and student achievement is good. WLB can influence student achievement positively and significantly by 23.23%. Student motivation cannot moderate the influence of WLB on student achievement because students' desire to study is not due to job demands. But because of parental demands or just getting a degree. So students don't pay too much attention to their work-life balance. Which has an impact on student motivation and cannot strengthen WLB in influencing student achievement. However, the partial test results are surprising that student motivation can influence student achievement.